PELATIHAN AKUPRESUR UNTUK RELAKSASI TUBUH DAN MENGATASI DISMENOREA - Wahyuningsih, Istiqomah Risa; Handayani, Sri (P3M STIKES Aisyiyah Surakarta, 2020)
Acupressure is a technique using touch / contact to balance the energy channels in the body or Qi. Acupressure contests useful for disease prevention, cure, rehabilitation (recovery), relaxation and increase endurance. Acupressure can also be used to treat pain during menstruation (dysmenorrhea). Target and outcome: an increase in knowledge and skills of women, the leaflets about the relaxation of the body and reduce dysmenorrhea, as well as community service articles published. Methods: divided into four sessions, namely working on the pretest, delivery of content and practice of acupressure, question and answer sessions working on the posttest. Submission of material is done by means of lectures and brainstorming as well as the demonstration of acupressure points used. Result: there is an increased knowledge of the pretest and posttest value of the average value before training (pre-test) 32.86 into 71.84 (post-test), in addition to the upgrading of skills seen from acupressure point positioning accuracy. Conclusion: The community service is to enhance the knowledge and skills of participants on acupressure to relax the body and overcome dysmenorrhoea.